Fundamental of Enterpreneurship (ENT 300) : Deisy Valet / Hazra Afira Marzuki … [et.al] - Marzuki, Hazra Afira; Apon, Loviana Mei; Abdul Rahman, Mohd Shafiq; Abdul Ghani, Nurhafieza; Zaidi, Zarith Tihani Nabihah (2018)
Deisy Valet is a place for our customers to find their favourite clothes and scarf where there is a variety of choices provided. We also offer our best product which is our own designed scarf where the scarfs do not have to be iron when the user wants to wear it. Our boutique will make our best to satisfy our customers and make them feel it worth it to shop at our boutique and at the same time will be the best boutique to be known around the world as comparable to other famous brands.